Optimization of Chaetoceros calcitrans (Paulsen) Takano 1968 biomass production via fed-batch culture mode - Muniandy, Kumari Geetha; Karim, Murni; Shariff, M.; Md Yusoff, Fatimah; Christianus, A.; Lim, Keng Chin (John Wiley and Sons, 2026)
This study investigated the effectiveness of adopting a fed-batch culture mode with intermittent feeding of culture media to enhance the biomass production of Chaetoceros calcitrans. Three experimental runs were undertaken, each comprising four cycles. The nutritional composition of the C. calcitrans biomass produced was evaluated. The experiment yielded a consistent production of C. calcitrans dry biomass, with outputs of 257.01, 251.88, and 252.41 g obtained in a cultivation period of 28 days per cycle. The initial inoculum concentrations for each run were high, measuring 4.2 × 107, 4.2 × 107, and 4.4 × 107 cells mL−1, respectively. A consistent increase in cell density and dry biomass was observed across all cycles. The cell density at the harvesting point was between 7.3 × 107 and 1.10 × 108 cells mL−1. The nutritional analysis of the C. calcitrans biomass revealed that protein comprised the largest proportion of the total biomass at 41.8 ± 0.7%, followed by carbohydrates at 27.2 ± 0.1% and lipids at 11.3 ± 0.6%. The biomass contained a total of 17 amino acids, comprising 43.2% essential amino acids and 56.7% non-essential amino acids, with the highest concentration observed for glutamic acid (17.6 ± 0.1%). The fatty acid composition of C. calcitrans was recorded with predominant polyunsaturated fatty acids (PUFAs) (44.6 ± 0.2%). The results suggest a possible cost-saving mechanism, as the culture mode adopted yielded higher microalgal biomass production while retaining a good range of nutritional profiles of C. calcitrans biomass.